Treatment and Outcome in Children With Tuberculous Meningitis: A Multicenter Pediatric Tuberculosis Network European Trials Group Study. (27th November 2021) - Thee, Stephanie; Basu Roy, Robindra; Blázquez-Gamero, Daniel; Falcón-Neyra, Lola; Neth, Olaf; Noguera-Julian, Antoni; Lillo, Cristina; Galli, Luisa; Venturini, Elisabetta; Buonsenso, Danilo; Götzinger, Florian; Martinez-Alier, Nuria; et al.
Abstract: Background: Currently, data on treatment, outcome, and prognostic factors in children with tuberculous meningitis (TBM) in Europe are limited. To date, most existing data on TBM originate from adult studies, or studies conducted in low-resource settings. Methods: We designed a multicenter, retrospective study involving 27 pediatric healthcare institutions in 9 European countries via an established pediatric TB research network, before and after the 2014 revision of World Health Organization (WHO) dosing recommendations. Results: Of 118 children, 39 (33.1%) had TBM grade 1, 68 (57.6%) grade 2, and 11 (9.3%) grade 3. Fifty-eight (49.1%) children received a standard 4-drug treatment regimen; other commonly used drugs included streptomycin, prothionamide, and amikacin. Almost half of the patients (48.3%; 56/116) were admitted to intensive care unit, with a median stay of 10 (interquartile range [IQR] 4.5–21.0) days. Of 104 children with complete outcome data, 9.6% (10/104) died, and only 47.1% (49/104) recovered fully. Main long-term sequelae included spasticity of 1 or more limbs and developmental delay both in 19.2% (20/104), and seizure disorder in 17.3% (18/104). Multivariate regression analyses identified microbiological confirmation of TBM, the need for neurosurgical intervention, and mechanical ventilation as risk factors for unfavorable outcome. Conclusions: There was considerable heterogeneity in the use of TB drugs in this cohort. Despite few children presenting with advanced disease and the study being conducted in a high-resource setting, morbidity and mortality were high. Several risk factors for poor outcome were identified, which may aid prognostic predictions in children with TBM in the future. Abstract : This European multicenter study provides data on the management and outcome of tuberculosis (TB) meningitis in children, highlighting that both morbidity and mortality remain high even in high-resource settings. Several key factors associated with unfavorable outcome were identified.